Underlying Causes and Co-existence of Malnutrition and Infections: An Exceedingly Common Death Risk in Cancer - Fan, Yuanyuan; Yao, Qianqian; Liu, Yufeng; Jia, Tiantian; Zhang, Junjuan; Jiang, Enshe (Frontiers in Nutrition, 2022)
In nutrition science, malnutrition is a state of imbalance between intake and the needs of the organism, leading to metabolic changes, impaired physiological functions and weight loss. Regardless of the countless efforts being taken and being researched for years, the burden of malnutrition is still alarming and considered a significant agent of mortality across the globe. Around 45% of 12 million children deaths (0-5 years old) annually are due to malnutrition, mostly from developing countries. Malnutrition develops associations with other infections and leads to substantial clinical outcomes such as mortality, more visits to hospitals, poor quality of life and physical frailty and socioeconomic issues. Here, in this review, we intend to provide an overview of the current burden, underlying risk factors, and co-existence of malnutrition and other infections including cancer. Following the rising concern of the vicious interplay of malnutrition and other medical illnesses, we believed that this narrative review would highlight the need to re-make and re-define the future strategies by giving comprehensive and sustainable programs to alleviate poverty and combat the rampant infectious diseases and those nutrition related health problems. Furthermore, the study also raises the concern for hospitalized malnourished cancer patients as it is crucially important to knowledge the caregiver healthcare staff for early interventions of providing nutritional support to delay or prevent the onset of malnutrition.